IMPLEMENTATION OF RESTORATIVE JUSTICE BASED ON DECREE OF THE DIRECTORATE GENERAL OF GENERAL JUSTICE AGENCY OF THE SUPREME COURT NUMBER 1691/DJU/SK/PS.00/12/2020 CONCERNING IMPLEMENTATION OF GUIDELINES FOR IMPLEMENTATION OF RESTORATIVE JUSTICE IN GENERAL - Meka Hawalia; Chandra Darusman S (Fox Justi : Jurnal Ilmu Hukum, 2022)
Restorative justice is one of the principles of law enforcement in resolving cases that can be used as an instrument of recovery and has been implemented by the Supreme Court in the form of policy enforcement (Supreme Court regulations and Supreme Court circulars) but its implementation in the Indonesian criminal justice system is still not optimal. .In this study, the type of research used is the Juridical Empirical approach. The research location used as a place to conduct research is the Sinabang District Court. Restorative justice is an alternative for resolving criminal cases which in the mechanism of criminal justice procedures focuses on punishment which is converted into a dialogue and mediation process involving the perpetrator, victim, family of the perpetrator/victim, and other related parties to jointly create an agreement and settle the case. fair and balanced criminal justice for both the victim and the perpetrator by prioritizing the restoration to its original state, and restoring the pattern of good relations in society.